고혈압 노인 환자에서 슬관절 수술 시 지혈대가 혈역학에 미치는 영향 - 김교상; Kyo Sang Kim; 민형기; Houng Ki Min; 윤홍준; Hong Jun Youn; 정미애; Mi Ae Cheong; 전종헌; Jong Hun Jun (Korean journal of anesthesiology, 2006)
Background: The hemodynamic and metabolic effects of tourniquet application undergoing knee surgery with general anesthesia in elderly patients with hypertension have been rarely reported. We evaluated the hemodynamic and metabolic effects in elderly patients compared with young adults. Methods: Thirty elderly patients (elderly hypertension group, 71.8 ± 3.9 years) with chronic hypertension undergoing total knee replacement and 30 young adults (normal group, 33.1 ± 5.1 years) undergoing knee surgery were studied. Mean arterial pressure (MAP), heart rate, cardiac index (CI) by esophageal doppler method, and systemic vascular resistance index (SVRI) were measured before, during, and after tourniquet application. pH, PaO2, PaCO2, Hb and lactate blood concentrations were also measured. Results: MAP increased 25% and 16% in elderly hypertension and normal groups during inflation, respectively (P ＜ 0.05) and returned to basal values after deflation. CI increased to 30% higher than basal values in both groups after deflation (P ＜ 0.05). SVRI decreased 31% and 19% in elderly hypertension and normal groups after deflation, respectively (P ＜ 0.05). After deflation, PaCO2 and lactate increased (P ＜ 0.05). Conclusions: Elderly patients with hypertension have the significant hemodynamic changes during and after tourniquet application than before, however, there are no differences compared to normal group. These elderly patients should be needed the active hemodynamic monitoring due to the lower compensatory ability. (Korean J Anesthesiol 2006; 51: 695~700)